2016
DOI: 10.7555/jbr.30.20140144
|View full text |Cite
|
Sign up to set email alerts
|

Association between TSHR gene polymorphism and the risk of Graves' disease: a meta-analysis

Abstract: Thyroid stimulating hormone receptor (TSHR) is thought to be a significant candidate for genetic susceptibility to Graves' disease (GD). However, the association between TSHR gene polymorphism and the risk of GD remains controversial. In this study, we investigated the relationship between the two conditions by meta-analysis. We searched all relevant case-control studies in PubMed, Web of Science, CNKI and Wanfang for literature available until May 2015, and chose studies on two single nucleotide polymorphisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In conjunction with exposure to environmental risk factors such as smoking, virus infection, iodine intake as well as use of certain drugs, genetically predisposed individuals are more likely to develop GD (2). So far, variations in several genes, in particular immune regulatory genes, have been found to be closely related with the development of GD, including CD40 (4), vitamin D receptor (5), PTPN22 (6), STAT4 (7), IL-6 (8), IL-2 (9), IL-2RA (10), IL-10 (11), TSHR (12,13), TG (14), and CTLA4 (15). Similar mechanisms could also be implicated in the pathogenesis of Graves' ophthalmopathy (GO), which affects up to half of the patients with GD.…”
Section: Introductionmentioning
confidence: 99%
“…In conjunction with exposure to environmental risk factors such as smoking, virus infection, iodine intake as well as use of certain drugs, genetically predisposed individuals are more likely to develop GD (2). So far, variations in several genes, in particular immune regulatory genes, have been found to be closely related with the development of GD, including CD40 (4), vitamin D receptor (5), PTPN22 (6), STAT4 (7), IL-6 (8), IL-2 (9), IL-2RA (10), IL-10 (11), TSHR (12,13), TG (14), and CTLA4 (15). Similar mechanisms could also be implicated in the pathogenesis of Graves' ophthalmopathy (GO), which affects up to half of the patients with GD.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, three meta-analysis studies intended to refine the effects of rs179247 and rs12101255 SNPs on GD susceptibility concluded that there is a significant association between these SNPs in TSHR intron 1 and GD (4446). …”
Section: Association Studiesmentioning
confidence: 99%